2013
DOI: 10.1155/2013/451715
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Multiple Focal Hole Segments Using Double-Ring Shaped Azimuthally Polarized Beam

Abstract: We investigated the focusing properties of a double-ring-shaped azimuthally polarized beam tightly focused with a high NA lens and a binary phase filter. We observe that by using 3 belts and 5 belts binary phase filters novel focal patterns including splitting of focal rings and multiring focus are obtained. We also found that a suitably designed phase structure can shift the focal rings along optical axis. The author expects such investigation is worthwhile for optical manipulation and material processing tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Here, for easy calculations, we presume that the refractive index n = 1, M(θ ) = 1, β = 1.2 and A = 1. Generally a double-ring-shaped azimuthally polarized beam without any phase modulation is tightly focused, a single-ring focal hole pattern is obtained (Lalithambigai et al 2013). It is reported that using SPM with a high NA lens one can generate a single transversely polarized bright focal spot (Yuan et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, for easy calculations, we presume that the refractive index n = 1, M(θ ) = 1, β = 1.2 and A = 1. Generally a double-ring-shaped azimuthally polarized beam without any phase modulation is tightly focused, a single-ring focal hole pattern is obtained (Lalithambigai et al 2013). It is reported that using SPM with a high NA lens one can generate a single transversely polarized bright focal spot (Yuan et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A "hollow dark channel" with a long focal depth was more recently achieved by tight focusing of a double-ring-shaped azimuthally polarized beam with additional high NA lens axicon system (Lalithambigai et al 2012). Multiple ring structure is also obtained by using azimuthally polarized beam with multibelt phase filter and high NA lens system, recently (Lalithambigai et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…J 1 ðxÞ is a symbol of the Bessel functions of the first kind and AðhÞ signifies the amplitude and phase distribution at the exit pupil. For an incident A-TEM p1 * beam, AðhÞ can be expressed as [18,19]:…”
Section: Theorymentioning
confidence: 99%
“…For example, radially polarized higher-order modes allow one to reduce the focal spot size [3,4] and thus to achieve super-resolution. Doublering structures with radial [5,6] or azimuthal [7] polarizations may exhibit advantages for optical trapping and manipulation. We propose to change the intensity ratio of the rings in order to optimize the strength of trapping and retention of transparent and opaque particles, and thus to perform their sorting.…”
Section: Introductionmentioning
confidence: 99%